Hepatitis C virus clearance correlates with HLA‐DR expression on proliferating CD8+ T cells in immune‐primed chimpanzees. Issue 3 (28th January 2014) - Zubkova, Iryna; Duan, Hongying; Wells, Frances; Mostowski, Howard; Chang, Esther; Pirollo, Kathleen; Krawczynski, Kris; Lanford, Robert; Major, Marian
<x xml:space="preserve">Abstract</x> Vaccination of chimpanzees against hepatitis C virus (HCV) using T‐cell‐based vaccines targeting nonstructural proteins has not resulted in the same levels of control and clearance as those seen in animals reexposed after HCV clearance. We hypothesized that the outcome of infection depends on the different subtypes of activated T cells. We used multicolor flow cytometry to evaluate activation (CD38+/HLA‐DR+) and proliferation (Ki67+/Bcl‐2‐low) profiles of CD4+ and CD8+ T cells in peripheral blood before and after challenge in chimpanzees vaccinated using DNA/adenovirus, mock‐vaccinated, and chimpanzees that had spontaneously cleared infection (rechallenged). The frequencies of activated or proliferating CD8+ T cells peaked at 2 weeks postchallenge in the vaccinated and rechallenged animals, coinciding with reductions in viral titers. However, the magnitude of the responses did not correlate with outcome or sustained control of viral replication. In contrast, proliferation of the CD8+ T cells coexpressing HLA‐DR either with or without CD38 expression was significantly higher at challenge in animals that rapidly cleared HCV and remained so throughout the follow‐up period. Conclusion: Our data suggest that the appearance of proliferating HLA‐DR+/CD8+ T cells can be used as a predictor of a successfully primed memory immune response against HCV and as a marker of effective vaccination in clinical trials. (Hepatology 2014;59:803–813)